Tes Diagnostik Miskonsepsi Peserta Didik pada Materi Tumbuhan Kelas IV Sekolah Dasar - Ariffia, Citrani Natha; Kurniawati, Wahyu (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2025)
This study aims to assess the level of misconceptions experienced by fourth-grade students at SD Muhammadiyah Kasuran and to identify the contributing factors behind these misconceptions. The findings of this identification process are expected to serve as a basis for designing appropriate and relevant solutions to overcome conceptual barriers in the learning process. The research adopts a descriptive quantitative approach, employing a diagnostic test as the primary data collection instrument. The subjects of this study include all fourth-grade students at SD Muhammadiyah Kasuran. Based on the analysis of diagnostic test data, it was found that the level of student misconceptions regarding the topic “Parts of a Plant” reached 56%. The same percentage was observed for the topic “Photosynthesis as the Most Important Process on Earth,” also at 56%. Meanwhile, the highest level of misconception was identified in the topic “Plant Reproduction,” with a rate of 64%. Several factors were suspected to be the main causes of these misconceptions, including: 1) Learning materials that do not adequately support students’ conceptual understanding; 2) Instructional strategies employed by teachers that remain conventional and unengaging, failing to stimulate active participation from students; and 3) Unfavorable classroom conditions, in which some students struggle to maintain focus and are easily distracted due to monotonous and non-interactive learning environments. These findings highlight the urgent need for improvements in instructional content delivery, the development of more innovative teaching methods, and the creation of more effective classroom management practices to minimize misconceptions among elementary school students.